If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(2*x+3)/5 = 9 // - 9
(2*x+3)/5-9 = 0
(2*x+3)/5+(-9*5)/5 = 0
2*x-9*5+3 = 0
2*x-42 = 0
(2*x-42)/5 = 0
(2*x-42)/5 = 0 // * 5
2*x-42 = 0
2*x-42 = 0 // + 42
2*x = 42 // : 2
x = 42/2
x = 21
x = 21
| 1-9x=0 | | (5y+5)-(2+4y)=9 | | 6x+7(2x-17)=41 | | 3(4x+6)=-35+41 | | 3x-2/5=x-2 | | b/9+1/4=11 | | 2x-6x-65=63 | | 3(2x+9)=5(x-2) | | 2AH=V^2-U^2 | | 6x-50=10x+73 | | -0.7x+0.8x+8=-2 | | 2ln(x)=ln(x+6) | | 3x=(4x-15) | | 2y+8y-3=x | | 5p-4=2p+12 | | 6.9x-6+x-1.6= | | 31=5t+6 | | 180+17n=350 | | 8-24=3y-2 | | 0.7+0.8+8=-2 | | V^2=U^2+2AH | | s=5r^3t | | 1/3x+6=-4 | | 3m-3=24 | | S=7+4s | | 7b+5-7b-2=8 | | 1/2x-1=-5 | | 3c+(c+12)=124 | | 4.5/5 | | 20=S+13-4s | | 3c+(c+12)=24 | | 0.25x+7.5-0.75x=3 |